Derek Fowler interviewed by Ann-Mari Jordens in the Chief Migration Officers' oral history project - Fowler, Derek, 1926-; Jordens, Ann-Mari, 1940- (2009)
Derek Fowler, born in Western Australia talks about his family background; childhood memories; his schooling; his WWII service; training as teacher under Commonwealth Reconstruction Training Scheme; War Service Homes scheme; training displaced persons from 1952 in Office of Education in Western Australia using Situational English; his time as a demonstration teacher at Claremont High School; becoming the only migrant education officer in Western Australia; the Commonwealth-State collaboration on migrant English; his marriage; his further education at University of Western Australia (1956-60); going to Nauru as headmaster and school inspector of primary schools (1961-62); return to Australia (1962); posting to Greece (1963) as Director of Language for Immigration Department to Intergovernmental Committee for European Migration (ICEM); pre-departure English language teaching by ICEM in residential schools; shipboard education; travels in Greece; relations with Australian Embassy, Greece; obtaining a Masters of Education degree at London School of Education in England (1966-67).
Fowler discusses his return to Australia (1967); joining Dept. of Immigration, Canberra (1970-72) as Commonwealth Coordinator of the Good Neighbour Movement; its establishment, aims, administration, funding arrangements and role; transferring to Department of Education as Director, Language Teaching Branch (1973); language testing for overseas students; language policy; being an observer at meeting of Southeast Asia Ministers for Education; the transfer of his Section to Schools Commission; liaison with Department of Immigration and radio stations about booklets for use in radio English language for migrants and involvement in early teaching of English through television; the changes 1950s-70s; English language teaching material for schools from 1971; Australia-wide language policy; Senate Committee on language policy, home tutor scheme; his retirement from Department of Education (1989); his post-retirement travel; his work with Australian War Memorial's restoration of Beaufort bombers since 1994; involvement in RSL.
Recorded on February 24, 2009 at Canberra, A.C.T.
Digital master available
National Library of Australia Pictures collection PIC Online access #NL40015
Timed summary (4 p.) and corrected transcript (typescript, 112 leaves)
Keywords: Fowler, Derek, -- 1926- -- Interviews; Australia. -- Department of Immigration -- Officials and employees; Good Neighbour Movement -- History; Australia -- Government policy -- Emigration and immigration; Australia -- Emigration and immigration -- History; Public servants